Estudo da ação danosa do glicerol em trocadores de calor casco-tubos em plantas de produção de biodiesel - Christ, Rudimar Lúcio (2014)
The proven benefits of biodiesel as fuel created and stimulated in Brazil a new segment of industry in the past few years, causing dozens of new plants of large-scale production were installed in diverse states. However, together with the production of this environmentally correct fuel, results as a byproduct glycerol, which has many applications and markets. Occurs that the processing of glycerol, immediately after its origination, presents problems especially in tube bundles of heat exchangers shell and tubes type. To evaluate this condition, a heat exchanger was created in small scale (prototype) and installed in a biodiesel production plant that was submitted to real process conditions. To obtain concrete answers about the situation, this prototype was instrumented such that the most important process variables could be monitored and the data stored for later evaluation. In order to expand the study, the tube bundle of the heat exchanger was built with four different materials, three of these materials where the most commonly stainless steels used by companies consulted, suppliers of biodiesel plants, and the last material which is an zirconium alloy, of use just yet diffused in this industry segment. The prototype equipment operated until that damage is no longer allowed over its operation, and as soon as it was removed from the biodiesel plant were checked an evaluation process of heat exchange tubes was initiated, where it was started beyond the visual characteristics, the roughness, thickness, and weight loss. All these parameters were compared with the conditions in which the tubes were in new condition, ie, before operating the equipment. The experimental procedure adopted proved to be efficient and instrumentation applied provided the data necessary for the study. Among the process parameters, the pH was the only one that showed large variations and found to be mainly responsible for limiting the lifetime of the test tubes, for low values, including near zero have been verified. It is also concluded that, among the tested materials, the SAF 2205 is the most suitable for test application while AISI 304 material is less adequate due to low resistance erosive-corrosive wear